TOXICITY OF AMMONIA TO THE LARVAE OF PENAEUS INDICUS H. MILNE EDWARDS - Jayasankar, P; Muthu, M S (Indian Journal of Fisheries, 2011)
Short-term experiments revealed a progressive increase in tolerance of the larval stages of Penaeus indicus to ammonia. 24-h LC30 values for nauplius, protozoea and mysis were 3.58 mg ammonia N/l (0.29 mg NH3-N/I), 17.86 mg ammonia- Nil (0.95 mg NHyN) and 46.01 mg ammonia-Nil O.lTmgNHj-N/I). respectively. 48-h LCjo value for protozoea was 16.8 mg ammonia-N per liter (1.18 mg NH3-N/I. Long-term chronic-toxicity experiments on nauplius to postlarva-1 showed that the 9-day incipient LCjo level was 11.99 ppm of ammonia-Nl (0.93 ppm NH3-N).